Eksplorasi Bakteri Dan Jamur Di Lingkungan Sekitar Sebagai Media Pembelajaran Biologi Di SMA Negeri 3 Menggala Kabupaten Tulang Bawang - Wawan Abdullah Setiawan; Bambang Irawan; Siti Sholekha; Andi Setiawan; Ardian (AMMA : Jurnal Pengabdian Masyarakat, 2026)
Biology education at the high school level frequently faces conceptualization constraints, where students receive microbiology material theoretically without direct connectivity to their surrounding ecosystems. The lack of microscope utilization skills and inadequate laboratory facilities are often the main obstacles for teachers in designing practical work. This community service program aims to improve the competence of 35 teachers at SMA Negeri 3 Menggala, Tulang Bawang Regency, in conducting proper microscopic observations of bacteria and fungi using samples from the surrounding environment. The activity was conducted on January 28, 2026, through a participatory-educative approach comprising theoretical presentations, demonstrations of making fresh preparations, and microscopic observation practices. Evaluation results using pre-tests and post-tests showed a significant increase in participants' cognitive understanding and technical skills, jumping from an initial 45% to 87%. Participants' enthusiasm was remarkably high during the activity. The school principal felt greatly assisted by this program as it provided practical solutions to optimize contextual and discovery-based biology learning without relying on expensive manufactured practicum kits .